Histochemical Studies on the Thymus of Pre and Postnatal Surti Goat (Capra hircus) - Shailendra Chaurasia (Indian Journal of Veterinary Anatomy, 2022)
Present study was conducted to elucidated some histochemical changes in the thymus of different age groups of prenatal and postnatal Surti goats. The Periodic-acid Schiff (PAS) reaction for the presence of glycogen was varying in different components of thymus in various age groups. The capsule and interlobular septa of thymus showed moderate to strong PAS positive reaction. Free epithelial reticular cells of cortex and medulla and Hassall’s corpuscles showed PAS positive activity in all age groups. The connective tissue framework of thymus showed weak to moderate alcian blue reaction. Hassall’s corpuscles were positive for acid mucopolysaccharides both in prenatal and postnatal age groups. A Positive Von Kossa’s reaction for the presence of calcium was observed in some Hassall’s corpuscles of postnatal Surti goats during 12 to 48 months.